Relationship Between Singing And Reading Together Activities With Children And Early Literacy Skill In Preschool Children In Surakarta - Sinar Perdana Putra; Muryanti, Muryanti; Windiarti Dwi Purnaningrum (Jurnal EduHealth, 2024)
In early childhood, early literacy skills can be started with the habit of reading story books. Although this is a simple activity, reading books is the initial stage of introducing them to literacy skills. Literacy is all activities that are seen in speaking, listening, reading, writing and singing are an appreciation of spoken and written language. While early literacy skills are skills that begin to develop in preschool. Early literacy skills are very important as they form the basis for more advanced reading and writing skills. Early literacy helps preschoolers understand and interpret the world around them through language and symbols, both in spoken and written form. Early literacy can help children's language development because it prepares reading and writing skills, develops communication skills, enhances imagination and creativity, supports cognitive development, and strengthens self-confidence. This study aims to describe, know, and analyze the relationship between singing and reading together activities with children and early literacy skill in preschool children in surakarta. The type of research is quantitative descriptive. The population in this study were preschool children from several kindergartens in Surakarta, Nusukan sub-district. The sample in this study was 177 preschool children. Data collection with questionnaires and tests. Data analysis using Multiple Linear Regression (MLR). The results of the analysis obtained a significance value (p-value) of 0.000. The significance value of the test is less than 0.05 (0.000 < 0.05) so that there is a significant relationship between singing and reading together activities with children and early literacy skills in preschool children in Surakarta.